The direct digital workflow in fixed implant prosthodontics: a narrative review - George Michelinakis; Dimitrios Apostolakis; Phophi Kamposiora; George Papavasiliou; Mutlu Özcan (BMC, 2021)
Abstract Background The purpose of this narrative review was to examine the applicability of IOS procedures regarding single and multiple fixed implant restorations. Clinical outcomes for monolithic zirconia and lithium disilicate restorations produced through a direct digital workflow were reported. Methods A MEDLINE (Pubmed) search of the relevant English-language literature spanning from January 1st 2015 until March 31st 2020 was conducted. In vitro studies comparing digital implant impression accuracy by different IOS devices or in vitro studies examining differences in accuracy between digital and conventional impression procedures were included. Also, RCTs, clinical trials and case series on the success and/or survival of monolithic zirconia and lithium disilicate restorations on implants, manufactured completely digitally were included. In vitro and in vivo studies reporting on restorations produced through an indirect digital workflow, case reports and non-English language articles were excluded. The aim was to investigate the accuracy of IOS for single and multiple fixed implant restorations compared to the conventional impression methods and report on the variables that influence it. Finally, this study aimed to report on the survival and success of fixed implant-retained restorations fabricated using the direct digital workflow. Results For the single and short-span implant sites, IOS accuracy was high and the deviations in the position of the virtual implant fell within the acceptable clinical limits. In the complete edentulous arch with multiple implants, no consensus regarding the superiority of the conventional, splinted, custom tray impression procedure compared to the IOS impression was identified. Moreover, complete-arch IOS impressions were more accurate than conventional, non-splinted, open or close tray impressions. Factors related to scanbody design as well as scanner generation, scanning range and interimplant distance were found to influence complete-arch scanning accuracy. Single implant-retained monolithic restorations exhibited high success and survival rates and minor complications for short to medium follow-up periods. Conclusions The vast majority of identified studies were in vitro and this limited their clinical significance. Nevertheless, intraoral scanning exhibited high accuracy both for single and multiple implant restorations. Available literature on single-implant monolithic restorations manufactured through a complete digital workflow shows promising results for a follow-up of 3-5 years.